News or animal spirits? Consumer confidence and economic activity: Redux - Sangyyup Choi; Jaehun Jeong; Dohyeon Park; Donghoon Yoo (Bank of Finland, 2023)
Barsky and Sims (2012, AER) demonstrated, via indirect inference, that confidence innovations can be viewed as noisy signals about medium-term economic growth. They highlighted that the connection between confidence and subsequent activity, such as consumption and output, is primarily driven by news shocks about the future. We expand upon their research in two significant ways. First, we incorporate the Great Recession and ZLB episodes, and second, we employ unique state-level data to offer insights into how to interpret the relationship between consumer confidence and economic activity. Our results confirm the main finding of Barsky and Sims (2012) that this relationship is predominantly driven by news about the future.
Keywords: E12; E21; E31; E32; E71; 330; Consumer confidence; news; animal spirits; Great Recession; state-level analysis